2022
DOI: 10.3389/fnins.2022.860368
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 2′-Fucosyllactose and Bifidobacterium longum Subspecies infantis Supplementation on Cognitive and Structural Brain Development in Young Pigs

Abstract: Development of the gut-brain axis during early-life is an important contributor of brain structural and functional development. Human milk oligosaccharides and gut microbiota have potential beneficial effects on various aspects of development; however, the effects of 2′-fucosyllactose (2′-FL) and Bifidobacterium longum subsp. infantis Bi-26 (Bi-26) administration during infancy separately and combined are still not clear. Therefore, we investigated the effects of early administration of dietary 2′-FL and Bi-26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 72 publications
3
5
0
Order By: Relevance
“…20 Some studies showed that dietary intervention with 2′-FL significantly influenced cognitive domains, thereby enhancing learning and memory in rodents. 21−23 tiation in young pigs, 24 indicating a direct impact on neurons within the central nervous system, which is consistent with the observed enhancement of memory consolidation in rodent studies.…”
Section: Introductionsupporting
confidence: 83%
“…20 Some studies showed that dietary intervention with 2′-FL significantly influenced cognitive domains, thereby enhancing learning and memory in rodents. 21−23 tiation in young pigs, 24 indicating a direct impact on neurons within the central nervous system, which is consistent with the observed enhancement of memory consolidation in rodent studies.…”
Section: Introductionsupporting
confidence: 83%
“…In a study on the 2'fl, solely or in combination with Bifidobacterium longum subsp. infantis (Bi-26), on cognitive and structural development in young pigs (Sutkus et al, 2022), the authors noted that synbiotic administration of 2'FL and Bi-26 had several interactive effects on microstructural brain components, however it appeared to have no effect on memory. Preclinical in vitro and in vivo studies propose that both 2′FL and LNnT promote the growth of several Bifidobacterium and Bacteroides species, strains, and subspecies including Bifidobacterium longum subsp.…”
Section: Human Milk Oligosaccharides Health Benefits and Clinical Datamentioning
confidence: 99%
“…9 A recent study has indicated that supplementation with 2'-FL could promote cognitive and structural brain development in young piglets. 10 Overall, these studies hinted that 2'-FL could be used to modulate gut microbiota and maintain gut health in pig production. Generally, 2'-FL cannot be degraded by the enzymes secreted by the host but can be utilized by the large intestinal microbiota.…”
Section: Introductionmentioning
confidence: 97%
“…In mice, 2'‐FL could ameliorate chemotherapy‐induced intestinal mucositis by protecting intestinal epithelial cells against apoptosis 9 . A recent study has indicated that supplementation with 2'‐FL could promote cognitive and structural brain development in young piglets 10 . Overall, these studies hinted that 2'‐FL could be used to modulate gut microbiota and maintain gut health in pig production.…”
Section: Introductionmentioning
confidence: 99%